The 2nd IEEE International Workshop on Wireless and Mobile Technologies in Education, 2004. Proceedings.
DOI: 10.1109/wmte.2004.1281375
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative note taking

Abstract: Collaborative note taking enables students in a class to take notes on their PDAs and share them with their "study group" in real-time. Students receive instructor's slides on their PDAs as the instructor displays them. As the individual members of the group take notes pertaining to the slide being presented, their notes are automatically sent to all members of the group. In addition, to reduce their typing, students can use text they receive from other students and from the instructors slides to construct the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Notepals [5] is a system for note-taking on Personal Digital Assistants (PDAs), but collaborative review of lecture notes takes place only after the notes have been uploaded onto a "Notepals" website following the lecture. A recent system [19] supports live collaboration on PDAs but with a fraction of the affordances of Livenotes.…”
Section: Motivationmentioning
confidence: 99%
“…Notepals [5] is a system for note-taking on Personal Digital Assistants (PDAs), but collaborative review of lecture notes takes place only after the notes have been uploaded onto a "Notepals" website following the lecture. A recent system [19] supports live collaboration on PDAs but with a fraction of the affordances of Livenotes.…”
Section: Motivationmentioning
confidence: 99%
“…A pilot study indicated added value for learning. Collaborative note taking (Singh et al, 2004) enables students in a class to take notes on their PDAs and share them with their 'study group' in real time. The system has been evaluated in a graduate-level course and has proved to be a helpful utility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singh et al proposed a system whereby users take notes using PDAs and then share these with their group in real time [8]. In order to reduce the amount of typing while constructing notes, students can use the text they receive from other students and from the instructors' slides.…”
Section: Related Workmentioning
confidence: 99%